Dying to win : the strategic logic of suicide terrorism - Pape, Robert Anthony, 1960- (Melbourne : Scribe, 2005)
A study of suicide terrorism analyzes the motivations behind the phenomenon, charting incidents of suicide terrorism around the world, examining key patterns in the events, and outlining ways in which governments can fight them.
Introduction. The growing threat -- Explaining suicide terrorism -- pt. 1. The strategic logic of suicide terrorism. A strategy for weak actors -- Targeting democracies -- Learning terrorism pays -- pt. 2. The social logic of suicide terrorism. Occupation and religious difference -- Demystifying al-Qaeda -- Suicide terrorist organizations around the globe -- pt. 3. The individual logic of suicide terrorism. Altruism and terrorism -- The demographic profile of suicide terrorists -- Portraits of three suicide terrorists -- Conclusion. A new strategy for victory -- Acknowledgments -- Appendix I. Suicide terrorist campaigns, 1980-2003 -- Appendix II. Occupations by democratic states, 1980-2003 -- Appendix III. Salafism in major Sunni Muslim majority countries.
Includes bibliographical references : (pages [279]-316) and index.
Keywords: Terrorism -- Psychological aspects; Terrorists -- Suicidal behavior; Terrorism -- Prevention